2020
DOI: 10.1088/1755-1315/564/1/012088
|View full text |Cite
|
Sign up to set email alerts
|

Low salinity reduces survival rate of a commercially important sea cucumber (Sandfish: Holothuria scabra)

Abstract: Sandfish culture had been implemented for more than 20 years but has frequently failed to yield the expected results due to low survival rates. A decrease in salinity during the rainy season was suspected as a cause of sandfish mortality. This study aimed to assess the influence of salinity on sandfish survival rates. Treatments included sudden shock and gradual acclimation trial methods. Even though the results of this study indicate a mean survival rate of 50% at 14.6 ppt, the survival rate fell drastically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, salinities of 28–34 ppt are preferred for the growth of another sea cucumbers, Holothuria scabra (Asha et al, 2011). A report indicated that salinity has severe impacts on survival rate (Tuwo et al, 2020), ion homeostasis and histological structure (Geng et al, 2016), ionic gradients and tissue hydration (Castellano et al, 2016), and growth and respiration (Bai et al, 2015; Russell, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, salinities of 28–34 ppt are preferred for the growth of another sea cucumbers, Holothuria scabra (Asha et al, 2011). A report indicated that salinity has severe impacts on survival rate (Tuwo et al, 2020), ion homeostasis and histological structure (Geng et al, 2016), ionic gradients and tissue hydration (Castellano et al, 2016), and growth and respiration (Bai et al, 2015; Russell, 2013).…”
Section: Introductionmentioning
confidence: 99%